2000
DOI: 10.1210/endo.141.5.7529
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Induced Cardiac Aldosterone Synthesis Causes Cardiac Hypertrophy

Abstract: High sodium intake causes cardiac hypertrophy independently of increases in blood pressure. Aldosterone is synthesized in extraadrenal tissues such as blood vessels, brain, and heart. Effects of 8 weeks of high sodium intake on cardiac aldosterone synthesis, as well as cardiac structure, mass, and aldosterone production, levels of mRNA coding for aldosterone synthase (CYP11B2) and the angiotensin II AT1 receptor, were studied in normotensive Wistar-Kyoto (WKY) rats. Isolated rat hearts were perfused for 2 hr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
3
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(38 citation statements)
references
References 0 publications
0
32
3
3
Order By: Relevance
“…As demonstrated by Takeda et al (19), an increased activity and tissue synthesis of aldosterone was observed in normotensive rats fed a high-sodium diet for 8 wk after weaning. In addition, the mineralocorticoid receptor antagonist spironolactone was shown to prevent the development of left ventricular hypertrophy and fibrosis induced by 8-wk feeding of adult Wistar rats with an 8%-NaCl diet (9).…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…As demonstrated by Takeda et al (19), an increased activity and tissue synthesis of aldosterone was observed in normotensive rats fed a high-sodium diet for 8 wk after weaning. In addition, the mineralocorticoid receptor antagonist spironolactone was shown to prevent the development of left ventricular hypertrophy and fibrosis induced by 8-wk feeding of adult Wistar rats with an 8%-NaCl diet (9).…”
mentioning
confidence: 61%
“…At variance with Wistar (9), Wistar Kyoto, and spontaneously hypertensive rats (23), no clear enhancement of fibrosis was detected in the Sprague-Dawley rats, despite a longer duration of high sodium feeding. Although the circulating renin activity drastically fell during high sodium intake, an enhanced activity and expression of the renin-angiotensin system were reported in cardiac (8,19) and vascular tissue (12). On the contrary, a low-sodium diet entirely prevented the cardiac hypertrophy associated with chronic infusion of ANG II (14), thus suggesting a role for tissue ANG II in the response of the cardiovascular system to salt intake changes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Aldosterone blockers have been reported to suppress cardiac hypertrophy and cardiac fibrosis (27,28). Takeda et al reported that a high-salt intake accelerates the expression of the aldosterone synthase gene, CYP11B2 mRNA, in the cardiac tissues while also increasing cardiac aldosterone synthesis locally, which may affect cardiac hypertrophy independently of the RAAS in blood (29). Recently, Ye et al reported that the CYP11B2 and 11尾-hydroxylase (CYP11B1) genes are not expressed in the rat heart (30).…”
Section: Discussionmentioning
confidence: 99%